Effect of Steaming Up on Old Pregnant Parent Weights, Calf Birth Weight and Colostrum Production in PFH Cattle in Sumber Rejeki Group, Princi, Dau, Malang District - Primasatya Nugraha; Puguh Surjowardojo (Bantara Journal of Animal Science, 2022)
The study purpose to determine the relationship between steaming up on body weight of pregnant cow, birth weight of calf and colostrum production. The research was conducted in Sumber Rejeki Group at Princi Village, Dau Sub-District, Malang Regency, East Java. The material used in this research was 30 cows. The research method used in this research was case study. The results showed that steaming up treatment did not give significant effects on body weight of pregnant cow and calf bir but it did give significant effects on colostrum production. The average weight of pregnant cow that treated with steaming up was 483.03±28.43 kg and the average weight that not treated with steaming up was 471.81±29.90 kg. The average calf birth weight that its mother treated with steaming up was 32.25±6.52 kg and the average calf birth weigh that its mother not treated with steaming up was 31.70±4.96 kg. The average of colostrum production from cow that treated with steaming up was 10.91±3.38 litre/cow/day and the average of colostrum production from cow that not treated with steaming up was 7.94±1.79 litre/cow/day. It was concluded that steaming up treatment effects on body weight of pregnant cow and calf birth weight did not differ significantly (p-value>0.05) but it had significant effects on colostrum production (p-value<0.05). It was suggested to have steaming up treatment on pregnant cow 2 until 3 weeks or 15 days before partus in order to achieve optimum production and maximum profit.